Anti-cancer Drugs Associated Atrial Fibrillation—An Analysis of Real-World Pharmacovigilance Data - Ahmad, Javaria; Thurlapati, Aswani; Thotamgari, Sahith; Grewal, Udhayvir Singh; Sheth, Aakash Rajendra; Gupta, Dipti; Beedupalli, Kavitha; Dominic, Paari (Frontiers in Cardiovascular Medicine, 2022)
Background Several anti-cancer drugs have been linked to new onset atrial fibrillation (AF) but the true association of these drugs with AF is unknown. The FDA Adverse Event Reporting System (FAERS), a publicly available pharmacovigilance mechanism provided by the FDA, collects adverse event reports from the United States and other countries, thus providing real-world data. Objectives To identify anti-cancer drugs associated with AF using the FAERS database. Methods The FAERS database was searched for all drugs reporting AF as an adverse event (AE). The top 30 anti-cancer drugs reporting AF cases were shortlisted and analyzed. Proportional reporting ratio (PRR) was used to measure disproportionality in reporting of adverse events for these drugs. Results When analyzed for AF as a percentage of all reported AE for a particular drug, Ibrutinib had the highest percentage (5.3%) followed distantly by venetoclax (1.6%), bortezomib (1.6%), carfilzomib (1.5%), and nilotinib (1.4%). The percentage of cardiac AE attributable to AF was also highest for ibrutinib (41.5%), followed by venetoclax (28.4%), pomalidomide (23.9%), bortezomib (18.2%), and lenalidomide (18.2%). Drugs with the highest PRR for AF included ibrutinib (5.96, 95% CI= 5.70–6.23), bortezomib (1.65, 95% CI = 1.52–1.79), venetoclax (1.65, 95% CI = 1.46–1.85), carfilzomib (1.53, 95% CI = 1.33–1.77), and nilotinib (1.46, 95% CI = 1.31–1.63). Conclusions While newer anti-cancer drugs have improved the prognosis in cancer patients, it is important to identify any arrhythmias they may cause early on to prevent increased morbidity and mortality. Prospective studies are needed to better understand the true incidence of new onset AF associated with anti-cancer drugs.